GAMBARAN POLA ASUH IBU DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS LIMAPULUH - Yulnefia Yulnefia; S.M Alfikri (LPPM Universitas Abdurrab, 2024)
Stunting is a growth disorder in toddlers due to prolonged nutrition deficiency. In 2022, the prevalence of stunting in Pekanbaru increased to 16,8%. Based on the 2022 from Pekanbaru Health Office, the highest prevalence of stunting was found in Limapuluh District, comprising of 60 toddlers. This was proven by a pilot study in Limapuluh Health Center with a stunting prevalence of 4,47%. Various factors affect stunting, including maternal parenting. Aside from affecting nutrition, parenting will also affect children’s psychosocial stimulus, health care, and health practice at home. Poor maternal parenting leads to poor nutrition, which in turn will cause stunting. Poor management will lead to short and long-term detrimental effects. This was an observational analytics study that uses a cross-sectional design. The study was conducted within the work area of Limapuluh Health Center Pekanbaru. Samples were obtained with the proportionate stratified random sampling technique with a total sample of 142. Univariate and bivariate analyses were used for data analysis using Chi-Square statistical test. To determine the correlation between maternal parenting and the risk of stunting in 12-23 months toddlers in the work area of Limapuluh Health Center Pekanbaru. There was a correlation between maternal parenting and the risk of stunting in 12-23 months old toddlers in the work area of Limapuluh Health Center Pekanbaru with a p- value of 0,027 and a PR value of 1,826. Maternal parenting was related and was a risk factor for stunting in 12-23 months old toddlers in the work area of Limapuluh Health Center Pekanbaru.